Revision of the myrmecophilous diapriid genus Bruchopria Kieffer (Hymenoptera, Proctotrupoidea, Diapriidae) - Loiácono, Marta Susana (2002)
A redescription of the genus Bruchopria and its two species, B. hexatoma Kieffer (female and male) and B. pentatoma Kieffer (male only) is presented. New record for B. hexatoma from Argentina is provided. Some aspects of diapriid biology with emphasis on their myrmecophilic evidence and association with ants are discussed. Scanning photographs of morphological structures are included.